2019
DOI: 10.4322/acr.2018.069
|View full text |Cite
|
Sign up to set email alerts
|

Bullous systemic lupus erythematosus a case report

Abstract: Skin involvement in systemic lupus erythematosus (SLE) occurs in more than 75% of patients with this condition. Vesicles and blisters in lupus erythematosus (LE) may be present in SLE secondary to interface vacuolar changes in the epidermis, in discoid LE also secondary to vacuolar epidermal changes, and in bullous LE secondary to antibodies anti-collagen VII deposits with neutrophilic aggregates. In addition, blisters can occur due to the association of SLE with other autoimmune blistering diseases (e.g. bull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 29 publications
(29 reference statements)
1
14
1
2
Order By: Relevance
“…Mucosal involvement is common in the laryngeal, pharyngeal, perioral, and genital areas. The lesions usually develop with no scarring, but hyper or hypochromia can occur (7). Here we believed that this case report will receive the most attention from Sudanese clinicians and rekindle knowledge and awareness in regard to vesiculobollous disease in patient who is known to be suffering from SLE.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Mucosal involvement is common in the laryngeal, pharyngeal, perioral, and genital areas. The lesions usually develop with no scarring, but hyper or hypochromia can occur (7). Here we believed that this case report will receive the most attention from Sudanese clinicians and rekindle knowledge and awareness in regard to vesiculobollous disease in patient who is known to be suffering from SLE.…”
Section: Introductionmentioning
confidence: 77%
“…The incidence of this disease with SLE is about 1%. As the knowledge about it is mainly based on case series or reports (7,9). Patients with the vesiculobullous disease usually present with clinical features of SLE, the blisters mainly occur on the oral mucosa, neck, face and upper extremities (10).…”
Section: Discussionmentioning
confidence: 99%
“…14 Ocorre preferencialmente no sexo feminino, sendo rara na faixa etária pediátrica, e possuindo caracteristicamente a presença de vesículas ou bolhas sob máculas ou pápulas eritematosas. 15 Em nosso estudo, verificamos prevalência de 1,88% e relação entre sexos de 5:1, entretanto a idade média de acometimento observada foi baixa, ainda que na faixa adulta, quando comparada com outros estudos.…”
Section: Discussionunclassified
“…18 Existem teorias que tentam relacionar fisiopatologicamente desordens autoimunes, como o vitiligo, com alguns tipos específicos de lúpus cutâneo, especialmente o bolhoso, mas a literatura ainda carece de dados confirmatórios. 15,19 Algumas doenças encontradas neste estudo, como acne, que surgiram associadas ao LEC, podem ser mais concernentes à faixa etária e a fatores de risco de surgimento de outras afecções cutâneas.…”
Section: Discussionunclassified
“…Among these lesions, BSLE is observed only in less than 1% of cases [5,6]. The first well-documented case of BSLE was published by Hall RP et al, in 1982 [7]; since the majority of cases are reported as sporadic observation or small series not exceeding ten cases [4][5][6][7][8][9][10]. Indeed, the latest systemic review of the world literature by de Risi T et al, in 2017 found only 118 published cases of BSLE [8].…”
Section: Discussionmentioning
confidence: 99%